Employment contracts and the Rome Convention: the Koelzsch ruling of the European Court of Justice - Zanobetti, Alessandra (CUADERNOS DE DERECHO TRANSNACIONAL, 2011)
With its decision of 15 March 2011 in the Koelzsch proceedings, the Court of Justice of the European Union expressed itself on the interpretation of Article 6(2) of the Rome Convention, which determines the law governing employment contracts in the absence of a choice, whose protective rules prevail over the application of the chosen law. In this case, the employee being an international truck driver, the nature of his activity rendered the question a controversial one. In the light of its case law, albeit ruled in the context of the Brussels Convention and the Brussels I Regulation, and having taken into account that the objective of Article 6 is to guarantee the employees adequate protection, the Court stated that a broad meaning of the connecting factor «the law of the country in which the employee habitually carries out his work in performance of the contract» needed to be adopted. Consequently, this reduces the operative space for the subsequent connecting factor of «the place of business through which [the employee] was engaged». This note, having illustrated and commented the case at hand and the decision of the Court, draws some suggestions on its contribution in determining the law governing employment relationships when establishing the country where the work is performed may be difficult, both under the Rome Convention as well as under the Rome I Regulation that has replaced it.